Analysis of Related Factors With the Activity of the Larva Monitoring Officer in Disease Control Efforts Dengue Hemorrhagic Fever In Tangerang District - Wahidin Wahidin; Muchtaruddin Mansyur; Rustika Herman (JUMP Health (Journal of Ultimate Public Health), 2018)
None